Charts, Calendars, Questionnaires & Intake Forms: Navigating the Options when Caring for Patients with Migraine - Aderinto, Nicholas; Nigam-Aggarwal, Minali; Madan, Sameer; Begasse de Dhaem, Olivia (Current neurology and neuroscience reports, 2025)
Purpose of Review To describe the different options available to collect clinical data for headache care via intake forms, questionnaires, diary, and electronic health record (EHR) and practical ways to optimize clinic flow and data integration in this era of information overload. Recent Findings Digital technologies can be leveraged to help with data integration and processing of information. Summary New technologies and progress with data integration have the potential to help streamline flow and improve healthcare outcomes. The benefits of new technologies must be weighed against potential ethical risks such as widening of healthcare disparities especially for those without English proficiency, technology proficiency, and those without access to internet. Concerns regarding data privacy and the potential commercialization of patient data must be addressed. The optimization of tracking tools, EHR-patient interfaces, and data integration across software is an area of ongoing work.